(untitled) (SAARC Journal of Agriculture, 2024)
Climate smart agriculture (CSA) aims to improve food security, help communities adapt to climate change and contribute to climate change mitigation by adopting appropriate practices. Attitude is a psychological tendency that is expressed by evaluating a particular entity with some degree of favour or disfavour. Therefore, this study aims to assess the extent of attitude of farmers toward CSA and explore the contributions of the selected characteristics of the coastal farmers to their attitude. Data were collected by using an interview schedule from 354 coastal farmers of 3 districts namely, Satkhira, Khulna and Bagerhat through Multistage Random Sampling Method during December 2021 to March 2022. Descriptive and inferential statistics were applied. To explore the contribution of the predictor variables to the outcome variables, full model regression analysis was employed. Results indicate that the highest proportion (61.01%) of the farmers had medium favourable attitude towards CSA as compared to 18.65% and 20.34% having low favourable and high favourable attitude towards CSA respectively. Farmers’ education, annual agricultural income, training exposure, benefit obtained from CSA and knowledge on CSA had positive significant contributions to their attitude toward CSA. On the other hand, farm size and decision-making ability had negative contributions to their attitude toward CSA. For wider adoption of CSA may require farmers’ capacity building through non-formal education, more exposure to training and proper knowledge. SAARC J. Agric., 22(1): 243-255 (2024)